X+35=3x(2x-3)

Simple and best practice solution for X+35=3x(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+35=3x(2x-3) equation:


Simplifying
X + 35 = 3x(2x + -3)

Reorder the terms:
35 + X = 3x(2x + -3)

Reorder the terms:
35 + X = 3x(-3 + 2x)
35 + X = (-3 * 3x + 2x * 3x)
35 + X = (-9x + 6x2)

Solving
35 + X = -9x + 6x2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + X = -9x + -35 + 6x2

Combine like terms: 35 + -35 = 0
0 + X = -9x + -35 + 6x2
X = -9x + -35 + 6x2

Reorder the terms:
X = -35 + -9x + 6x2

Simplifying
X = -35 + -9x + 6x2

See similar equations:

| 132=3x+12 | | 64+76+69+x/4=70 | | (5x/6)-(x/3)+1=(8/9) | | 1.95k=1016+k | | 14=3 | | (5/6)-64=96 | | (5t-5/-10)=70 | | -9+x=-31 | | 5+6x=70 | | arcsinx=1 | | (m/-6)+6=41 | | arcsin=1 | | ln(3x)+ln(5x)=0 | | 8=(c/-4)+6 | | 2a^3*(-7a^5)= | | -2.5(-3y+9)+0.2y= | | 42x+4+58x-2=42 | | tgx=3 | | (s/19)=50 | | 91+x+x+79=148 | | (5x-7)-(6x+6)=27 | | 7*-19=-3*-3 | | (X/2)+(4/5)=9/12 | | 26/5+26/3r=5/3r-(-r-1/5) | | (n/-19)=76 | | (a+3)*5-(2a+8)*2=5 | | 9(x+5)-9=39-5x-3+14x | | 3+24x+14x+8=45 | | -3+11/4p=-7/4p-1/2(7p+4) | | -8=b-2 | | -6z-4(2-5z)=-22+10z | | b+10=-6 |

Equations solver categories